Optimal scheduling of an electric–hydrogen-integrated energy system considering virtual energy storage - Zhang, Bolin; Shao, Chong; Li, Chunhua; Guo, Tingzhe; Lei, Aihu; Guan, Xinyu; Zu, Longyu (Frontiers in Energy Research, 2024)
In this paper, a two-layer optimization approach is proposed to facilitate multi-energy comple-mentarity and coupling and to optimize the system configuration in an electric-hydrogen-integrated energy system. Firstly, an electric-hydrogen-integrated energy system with virtual energy storage is proposed to reduce the cost of physical energy storage equipment. Secondly, a twolayer optimal allocation method is proposed under a multi-timescale strategy to examine the comprehensive evaluation index of environmental protection and economy. The upper layer uses the NSGA-II multi-objective optimization method for system capacity allocation, and the lower layer performs economic dispatch at the lowest cost. Ultimately, the results of the equipment capacity allocation of the electric-hydrogen integrated energy system that satisfies the re-liability constraint interval and the scheduling results of the equipment within a day are output. The results show that the electric-hydrogen-integrated energy system with multiple energy equipment coupling not only improves the utilization of new energy units but also reduces fossil energy use and improves the system's reliability.